The Implementation of the Blended Learning Model: An Effort to Enhace Analytical Skills (C4) on the Topic of Exemplary Indonesian Islamic Scholars - Nurul Azizah; Nachua Qinanthi; Nadia Eka Sauwitri; Lepi Maya Sari; Mona Agustina; Anggraini Pratiwi (Action Research Journal Indonesia (ARJI), 2025)
The low scores of students in the Islamic Religious Education (IRE) subject, which have not yet met the Minimum Completeness Criteria (KKM), indicate challenges in the learning process. This study aims to examine the effectiveness of a blended learning model based on the Quizizz application on student learning outcomes at SMA Negeri 1 Katibung using a quasi-experimental method with a post-test only control group design and simple random sampling technique. The sample consisted of 63 eleventh-grade students divided into an experimental class using the blended learning model and a control class using a traditional learning model. The instrument used was a valid and reliable multiple-choice test administered after the treatment. Data analysis included normality test, homogeneity test, independent sample t-test, and Mann-Whitney U test. The results showed that the Sig. (2-tailed) value in Levene’s Test for Equality of Variances was 0.228 (>0.05), thus the null hypothesis Ho was accepted and the alternative hypothesis Ha was rejected, meaning that the Quizizz-based blended learning model was not effective in improving student learning outcomes. Therefore, teachers are advised to evaluate this learning model and consider alternative methods. The school is also recommended to provide training on learning technology for teachers. Researchers are encouraged to investigate other factors affecting learning outcomes and expand the scope of research. Furthermore, relevant parties are expected to support the use of technology through appropriate policies and adequate facilities.